Deep Sequencing of Viral Genomes Provides Insight into the Evolution and Pathogenesis of Varicella Zoster Virus and Its Vaccine in Humans - Depledge, Daniel P.; Kundu, Samit; Jensen, Nancy J.; Gray, Eleanor R.; Jones, Meleri; Steinberg, Sharon; Gershon, Anne; Kinchington, Paul R.; Schmid, D. Scott; Balloux, Francois; Nichols, Richard A.; Breuer, Judith (Molecular biology and evolution, 2014)
Immunization with the vOka vaccine prevents varicella (chickenpox) in children and susceptible adults. The vOka vaccine strain comprises a mixture of genotypes and, despite attenuation, causes rashes in small numbers of recipients. Like wild-type virus, the vaccine establishes latency in neuronal tissue and can later reactivate to cause Herpes zoster (shingles). Using hybridization-based methodologies, we have purified and sequenced vOka directly from skin lesions. We show that alleles present in the vaccine can be recovered from the lesions and demonstrate the presence of a severe bottleneck between inoculation and lesion formation. Genotypes in any one lesion appear to be descended from one to three vaccine-genotypes with a low frequency of novel mutations. No single vOka haplotype and no novel mutations are consistently present in rashes, indicating that neither new mutations nor recombination with wild type are critical to the evolution of vOka rashes. Instead, alleles arising from attenuation (i.e., not derived from free-living virus) are present at lower frequencies in rash genotypes. We identify 11 loci at which the ancestral allele is selected for in vOka rash formation and show genotypes in rashes that have reactivated from latency cannot be distinguished from rashes occurring immediately after inoculation. We conclude that the vOka vaccine, although heterogeneous, has not evolved to form rashes through positive selection in the mode of a quasispecies, but rather alleles that were essentially neutral during the vaccine production have been selected against in the human subjects, allowing us to identify key loci for rash formation.